The perils of print culture : book, print and publishing history in theory and practice - Patten, Eve; McElligott, Jason, 1972- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2014)
"This stimulating collection of essays illustrates various pressures and concerns - both practical and theoretical - related to research in the fast-developing terrain of print culture studies. As the editors Jason McElligott and Eve Patten suggest in an engaging and provocative introduction to the volume, researchers in diverse aspects of this field regularly confront similar procedural or methodological difficulties in their work: these range from doubts about the reliability of digitized resources and concerns with the limiting parameters of 'national' book history to overall skepticism about academic definitions of what 'print culture' means in the first place. In the essays assembled here, several leading print culture experts, including Leslie Howsam, James Raven, David Finkelstein and Toby Barnard, join with a number of emerging scholars and historians of print culture to address such 'perils', in a series of lively and illuminating 'case-study' contributions to the subject"--
Machine generated contents note: -- List of Illustrations -- Preface -- Notes on the Contributors -- 1. The Perils of Print Culture: An Introduction / Jason McElligott and Eve Patten -- 2. The Practice of Book and Print Culture: Sources, Methods, Readings / Leslie Howsam -- 3. 'Pretious treasures made cheap'? The Real Cost of Reading Roman History in Early Modern England / Freyja Cox Jensen -- 4. Early Printed Liturgical Books and the Modern Resources that Describe Them: The Case of the Hereford Breviary, 1505 / Matthew Cheung Salisbury -- 5. 'Lacking Ware, withal': Finding Sir James Ware Among the Many Incarnations of his Histories / Mark Williams -- 6. Balancing Theoretical Models and Local Studies: the Case of William St. Clair and Copyright in Ireland / Sarah Crider Arndt -- 7. The Impact of Print in Ireland, 1680-1800: Problems and Perils / T.C. Barnard -- 8. Signs of the Times? Reading Signatures in Two Late Seventeenth-century Secret Histories / Rebecca Bullard -- 9. Dangerous Detours: The Perils of Victorian Periodicals in the Digitized Age / Margery Masterson -- 10. Nineteenth-century Print on the Move: A Perilous Study of Trans-local Migration and Print Skills Transfer; David Finkelstein -- 11. The Problem with Libraries: The Case of Thomas Marshall's Collection of English Civil War Printed Ephemera / Annette Walton -- 12. The 'Lesser' Dürer? Text and Image in Early-modern Broadsheets / Cristina Neagu -- 13. 'Fair forms' and 'withered leaves': Rose Bud and the Peculiarities of Periodical Print / Anna Luker Gilding -- 14.'Print Culture' and the Perils of Practice / James Raven -- Index.
"This book arises from a conference entitled 'The Perils of Print Culture' organised ... at Trinity College Dublin in September 2010."
Includes bibliographical references and index.
Keywords: Printing -- History; Printing -- Social aspects -- History; Printing -- Great Britain -- History; Books -- History; Books -- Social aspects -- History; Books -- Great Britain -- History; Publishers and publishing -- History; Books and reading -- History